Survival Outcomes and Prognostic Predictors in Patients With Malignant Struma Ovarii - Li, Sijian; Kong, Shujun; Wang, Xiaoxue; Zhang, Xinyue; Yin, Min; Yang, Jiaxin (Frontiers in Medicine, 2021)
Background: Malignant struma ovarii (MSO) is an extremely rare ovarian malignant tumor and there is limited data on survival outcomes and prognostic predictors of MSO. The objectives of this study were to investigate the disease-free survival (DFS), overall survival (OS), and disease-specific survival (DSS) rates of patients with MSO, and also evaluate the prognostic factors in this population. Methods: A retrospective study was conducted and 194 cases of MSO were selected. DFS was assessed by the logistic regression, OS by the Kaplan-Meier method, and DSS was evaluated by the Cox regression. Results: The median age of these patients was 46.0 years; 142 cases (73.2%) were confined to the ovary and 52 cases (26.8%) had extra-ovarian metastasis at the initial diagnosis of MSO. During follow-up, 75.3% of these patients showed no evidence of disease and 18.0% were alive with disease. Only 13 deaths occurred, with 10 attributed to MSO. The 5-year, 10-year, and 15-year OS rates were 91.4%, 87.7%, and 83.5%, respectively. The 5-year, 10-year, and 15-year DSS rates were 93.8%, 90.0%, and 85.7%, respectively. Logistic regression revealed that FIGO stage IV was the only risk factor for DFS (P < 0.001; Odds Ratio [OR] 7.328; 95% confident interval [CI] 3.103 – 16.885, FIGO stage IV vs. stage I; P = 0.021; OR 4.750, 95% CI 1.264 – 17.856, FIGO stage IV vs. stage II-III). Multivariate Cox regression showed poor differentiation was the only risk factor for both OS (P = 0.005, OR 6.406; 95% CI 1.730 – 23.717) and DSS (P = 0.001, OR 9.664; 95% CI 2.409 – 38.760), while age ≥ 45 years was the prognostic predictor for OS (P = 0.038, OR 4.959; 95% CI 1.093 – 22.508). Conclusion: Survival outcomes were excellent in patients with MSO, irrespective of the treatment strategy, FIGO stage IV, age ≥ 45 years, and poor differentiation of tumors were the independent risk factors.